Effect of acute cadmium exposure on oxidative stress and antioxidant system of the scallop Aequipecten tehuelchus - Sturla Lompre, Julieta (2024)
This study aimed to assess the impact of acute exposure (96 h) to Cd in gills, digestive gland and muscle of the Tehuelche scallop Aequipecten tehuelchus from San José gulf in Patagonia, Argentina. Scallops were exposed to Cd concentrations of 0, 25, 50, 100, 150, 204, 275, 371, and 500 μg/L, and mortality rates were recorded after 96 h of exposure. Surviving organisms were analyzed for the biochemical response through reactive oxygen and nitrogen species (RONS), activities of catalase (CAT) and glutathione-S-transferase (GST), metallothioneins (MT), lipid peroxidation (LPO) and liposoluble antioxidants α-tocopherol (α-T) and β-carotene (β-C). The mean lethal concentration (LC50) was 155.8 μg Cd/L, a lower value than other scallops´ species, showing that A. tehuelchus has a particular sensitivity to Cd. In the three tissues, at all exposure concentrations, there was no significant response in RONS levels, GST activity or LPO. Nevertheless, CAT activity and α-T levels decreased in the gills but increased in the digestive gland, with no significant response in the muscle. Two-way ANOVA revealed a significant interaction between Cd concentration and tissue on MT, which increased significantly in gills, decreased in digestive gland with 100 compared to 50 μg Cd/L; whereas in muscle a significant increase was observed with 25 μg Cd/L compared to control. The results show a significant effect of Cd in scallop´s gills on CAT activity and α-T levels, highlighting this tissue as the primary target against relevant concentrations of metal in seawater. The effect on digestive gland and muscle was minimal. The overall results suggest that Cd toxicity is tissue-specific. This study will help reduce the existence knowledge gap regarding potential impacts of acute exposure to Cd in a bivalve species with high ecological and commercial importance, as well as identifying the most responsive biomarkers associated with Cd stress for monitoring assessment.